توظيف العامية في روايات واسيني الأعرج –رواية نساء كازانوفا أنموذجا– - سميحة, الأبيض; بلقاسم, دفة (جامعة الوادي - University of Eloued, 2021)
يعد واسيني الأعرج من الروائيين العرب الذين وصلت كتاباتهم إلى العالمية لما لها من تأثير على القارئ حيث تتصف بتعرية الحقائق ووصف الوقائع الاجتماعية والفكرية والأيديولوجية، وقد استعان في بنائه اللغوي بتقنيات فنية مميزة أنتجت خطابا جزائريا حديثا من حيث البناء واللغة التي مازج فيها بين اللغة الفصحى الفخمة الأنيقة واللغة العامية البسيطة، وقد وظف العامية في الحوار بين الشخصيات لتصور الواقع بكل آلامه وآماله وأمثاله التي تجري على ألسنته والأغاني الشعبية التي يرددها في أفراحه. وقد تناولنا الإشكالية الآتية: ما هو سياق الاهتمام باللغة؟ وهل وفق واسيني الأعرج في توظيف اللغة العامية؟ وهل هي الأقدر على تصوير الواقع وشخصياته؟ وهذا ما سنحاول الإجابة عنه في المقال الذي عنوناه بـ "توظيف العامية في رواية نساء كازانوفا لــ واسيني الأعرج أنموذجا" مبرزين قدرة الكاتب على توليد اللغة واستثمارها واستخدامها في أحسن الصيغ. Waciny Al-Araj is one of the Arab novelists whose writings have reached the world because of its impact on the reader, as it is characterized by denuding facts and describing social, intellectual and ideological facts, and his use in linguistic construction with distinctive artistic techniques that produced a modern Algerian discourse in terms of construction and language in which it mixed between the beauty and elegant classical and the simple colloquial language, and his use of the colloquial in the dialogue between the characters to visualize the reality with all its pains, hopes and proverbs that take place on his tongues and the popular songs he recites in festivals. We have delay with the problem: What is the context of interest in language? Does Waciny succeeded in the use of the vernacular? Is it the most capable of portraying reality and its characters? This is what we will try to answer in the article entitled “The Use of the Colloquial in the novel of Casanova Women by Wassini Laredj Al-Araj as a Model”, highlighting the writer's ability to generate language, invest it and use it in the best form..
Keywords: لغة الرواية، واسيني الأعرج، العامية، الحوار، الأمثال، الأغنية الشعبية، الخطاب الأدبي; novel language, Wassini Laredj, colloquial, dialogue, proverbs, popular song, literary discours